IN VITRO AND IN VIVO ANTIFUNGAL ACTIVITY OF ALKALOID 3,5-bis(4,4’’-dimethoxy- [1,1’:2’,1’’-terphenyl]-4’-yl)-4H-pyrazole-4,4-diol FROM DERRIS INDICA (LAM) BENNETT SEEDS - TABASSUM, NUZHAT; G. M., VIDYASAGAR; D, RAGHUNANDAN; I, SHIVAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The aim of the present study is to isolate an antifungal compound from Derris indica (Lam) Bennett seed oil with various solvents and evaluation of its antifungal activity against the clinical species of Candida. Methods: D. indica seed hexane extract was tested against Trichophyton rubrum, Trichophyton tonsurans and Candida albicans. Hexane extract was fractioned using different solvents through column chromatography (CC). Isolated compound D1 was identified and characterized using ultraviolet, Fourier-transform infrared, 1HNMR, and mass spectroscopy. In vitro evaluation of D1 carried out against 12 Candida strains. In vivo evaluation of D1 carried out against T. rubrum, T. tonsurans, and C. albicans using an excision wound healing model on male Wistar rats. Results: Different concentrations of hexane extract showed antimicrobial activity against tested microorganism with varying minimum inhibitory concentration values. On fractionation with hexane-petroleum ether through CC, it yielded a crystalline fraction. Compound D1 characterized as a 3,5-bis (4,4’’-dimethoxy-[1,1’: 2’,1’’-terphenyl]-4’-yl)-4H-pyrazole-4,4-diol. A novel alkaloid compound from D. indica is a new report and proved to be inhibitory against C. albicans MTCC 3017 (14.83±0.28), MTCC 1637 (16.0±0.0), Candida glabrata MTCC 3814 (16.83±0.28) and MTCC 3014 (16.66±0.57), Candida tropicalis MTCC 230 (20.0±0.0), MTCC 1406 (12.33±0.57). C. glabrata MTCC 3981 was found to be resistant to the compound. In vivo studies showed no visual symptoms at the end of treatment indicating the therapeutic property of the compound. Conclusion: The D1 was found to be effective against human fungal pathogens and can be used as a base molecule in designing new antifungal drugs.